2010
DOI: 10.1037/a0020089
|View full text |Cite
|
Sign up to set email alerts
|

Patient and health care provider views of depressive symptoms and diabetes in American Samoa.

Abstract: High type 2 diabetes prevalence, associated with recent cultural changes in diet and physical activity, characterizes the U.S. territory of American Samoa. Comorbid diabetes and depression rates are high worldwide and contribute to negative diabetes outcomes; these rates have not been assessed in American Samoa. In this study, six focus groups (FGs) were conducted with 39 American Samoan adults with diabetes; questions on perceptions of diabetes and depressive symptoms were included. Thirteen healthcare staff … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 39 publications
0
8
0
1
Order By: Relevance
“…The need for qualitative studies in minority groups is particularly significant because individual ethnic groups may experience depression symptomatology differently. 46 Based on individual and/or collective perceptions of depression of a given racial/ethnic group, preferred treatments for depression, as well as for diabetes, could differ. 46 Even for this review, ethnicity was not consistently reported.…”
Section: Discussionmentioning
confidence: 99%
“…The need for qualitative studies in minority groups is particularly significant because individual ethnic groups may experience depression symptomatology differently. 46 Based on individual and/or collective perceptions of depression of a given racial/ethnic group, preferred treatments for depression, as well as for diabetes, could differ. 46 Even for this review, ethnicity was not consistently reported.…”
Section: Discussionmentioning
confidence: 99%
“…The Precede-Proceed model also guided content, as each topic included three sections for: predisposing factors (exploring beliefs and motivation), enabling factors (building behavior change skills) and reinforcing factors (enlisting support from family, medical team and community). Cultural features identified during the formative research were incorporated, such as motivational quotes from focus groups, healthy local foods and exercise, examples of barriers to medication taking 27 , sources of stress and effective coping strategies 34 . Group visits also utilized flipchart content, as well as other teaching aids in Samoan language 35, 36 .…”
Section: Methodsmentioning
confidence: 99%
“…Diabetes mellitus (DM) is a significant public health problem associated with a high index of mortality and morbidity, including major depression . In fact, the prevalence of depression is approximately 10% in diabetic patients .…”
Section: Introductionmentioning
confidence: 99%